PENDAMPINGAN MEMBUAT DIGITAL MARKETING UNTUK PELAKU UMKM SUGI ORNAMEN - Mohamad Shodikur Rifqi; Aditya Pamungkas; Diana Khairuna; Kirana Zullfa Kamila; Ari Muhardono; Diani Syahrani (DIMASEKA, 2024)
This digital business mentoring aims to improve the ability of Ornament Sugi MSMEs to utilize digital technology for marketing and business development. This mentoring focuses on website development, social media management, and online sales strategies through e-commerce platforms. The mentoring methods used include theoretical and practical training, as well as ongoing mentoring. The results of this mentoring are expected to increase sales, market reach, and the competitiveness of Ornament Sugi MSMEs in the digital era. Further evaluation is needed to measure the long-term impact of this mentoring.